2011
DOI: 10.1016/j.jep.2010.08.062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bamboo extract on hepatic biotransforming enzymes – Findings from an obese–diabetic mouse model

Abstract: Aim of the study Bamboo leaves are used as a component in traditional Chinese medicine for the anti-inflammatory function. Our previous studies have demonstrated that an ethanol/water extract from Phyllostachys edulis ameliorated obesity-associated chronic systemic inflammation in mice, and therefore relieving the symptoms of type 2 diabetes. The aim of this project was to further investigate the effects of this bamboo extract on hepatic biotransformation enzymes in both lean and obese mice, as an initial step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…25 Our results showed that the expression of hepatic SULT 1A1 and SULT 2A1 mRNAs in diabetic rats were dramatically reduced compared with normal rats (Fig. 2E; p < 0.05).…”
Section: Effect Of Rtlw and Rtle On Phase II Enzymes In The Livers Ofmentioning
confidence: 52%
See 1 more Smart Citation
“…25 Our results showed that the expression of hepatic SULT 1A1 and SULT 2A1 mRNAs in diabetic rats were dramatically reduced compared with normal rats (Fig. 2E; p < 0.05).…”
Section: Effect Of Rtlw and Rtle On Phase II Enzymes In The Livers Ofmentioning
confidence: 52%
“…It was previously reported that the mRNA and protein levels of UGTs 1A1, 1A6, 1A7, 2B1, and 1A9 were reduced in livers of obese rats and mice. [23][24][25] Our results revealed that the expression levels of hepatic UGT 1A7 and UGT 2B1 mRNAs were signicantly decreased in HFD/STZ-induced diabetic rats ( Fig. 2A and 3B, p < 0.05).…”
Section: Effect Of Rtlw and Rtle On Phase II Enzymes In The Livers Ofmentioning
confidence: 63%
“…In the current study, catalytic activity detected using CDNB, the universal GST substrate, was lower in liver from obese animals than from lean mice. On the contrary, Koide et al (2011) reported higher total GST activity in obese/diabetic mice. Similar to our results, Roe et al (1999) reported lower GST activity in genetically obese (ob/ob) male mice than in lean counterparts.…”
Section: Catalytic Activitiesmentioning
confidence: 82%
“…In addition, a recent scientific paper focused on the anti-oxidant mechanism of bamboo extracts, which revealed that anti-oxidants from bamboo-protected cells against oxidative damage through induction of expression of phase II enzyme genes (Kweon et al, 2006). Furthermore, Koide et al (2011) found that bamboo extracts showed lesser regulatory effects on Phase II enzymes in comparison with those on Phase I enzymes. In the modern environment, Phase I and II enzymes are vital for cell survival because they catalyse the conversion of xenobiotic or reactive free radicals into less toxic products via oxidation or conjugation and provoke the expression of Phase II detoxifying genes.…”
Section: Discussionmentioning
confidence: 99%